Deepening of the World-System Crisis - Leonid Grinin; Anton Grinin (Journal of World-Systems Research)
Since the beginning of the Great Recession in 2008 the world-system has become increasingly in a state of crisis, which continues to deepen. Since Russia’s special military operation in Ukraine (SMO) in February 2022, the world-system has entered a new phase of development that combines international, economic and other crises. The geopolitical aspects of the world-system crisis and the consequences of the military conflict are now being actively debated, but there is almost no research on how these crises and military actions affect and will continue to affect the environmental situation in the region and in the world in general. In this paper we analyze different aspects and reasons and explain how and why the deepening crisis of the World-system has had and will have a negative impact on the ecology of the world.